High‐frequency pulse width modulation noise reduction for permanent magnet synchronous motors using hybrid asymmetrical regular sampled modified space‐vector pulse width modulation. Issue 3 (10th January 2021) - Zhang, Wentao; Xu, Yongxiang; Yu, Guodong; Zou, Jibin
Abstract: This paper proposes a strategy called hybrid asymmetrical regular sampled modified space‐vector pulse width modulation technique in two‐level voltage source inverters. Based on the existing modified space‐vector pulse width modulation, the presented strategy further changes the phase voltage waveform and carrier period, therefore not only eliminating the pulse width modulation noise nearby odd‐order carrier frequency but also reducing the noise around even‐order carrier frequency. Moreover, the frequency band is not elevated due to the periodical varying switching frequency. Under the condition of achieving similar high‐frequency harmonic performance, the proposed strategy will save at least 25% switching loss compared with conventional space‐vector pulse width modulation. Moreover, the dynamic performance of the drive system using the hybrid asymmetrical regular sampled modified space‐vector pulse width modulation can also be improved by asymmetrical regular sample. Implementation process has been introduced and the noise elimination principle has been analysed by mathematical demonstration. Finally, the effectiveness of the proposed strategy has been confirmed by simulation and detailed experimental results.